Could Apparent Diffusion coefficient (ADC) be used as an imaging marker for proliferative activity in breast carcinoma? - Jelena Marić; Jasmina Boban; Tatjana Ivković-Kapicl; Dragana Djilas; Viktorija Vučaj-Ćirilović; Dragana Bogdanović-Stojanović (Биомедицинска истраживања, 2023)
Introduction: Multiparametric magnetic resonance mammography (mMRM) has an important role in detection, evaluation and follow-up of breast lesions. The aim of this study was to explore whether imaging parameters, in particular ADC, can be used as a biomarker of cell proliferation in breast cancer. Methods: This cohort-study included 67 lesions in 50 female patients who underwent mMRM on a 3T scanner. Percutaneous biopsies and surgical excisions were performed after imaging in period up to 3 weeks. The Ki67 index was assessed microscopically. Seven Ki67 categories were defined: 0-5%, 10-20%, 20-40%, 40-50%, 50-80% and over 80%. Methods: of descriptive statistics were used; correlations were determined using Pearson’s correlation test. ROC curve was constructed and analyzed for determination of "cut-off" values for diagnostic potential. Statistical significance was set at p < 0.05. Results: Different subtypes of breast carcinomas were involved: ductal carcinoma (59.9%), lobular carcinoma (17.9%), metastatic carcinoma (10.5%), ductal carcinoma in situ (9%), and tubular carcinoma (3%). It was not possible to determine whether there was significant difference in values of ADC for histological subtypes of breast carcinoma because of small number of samples in some groups. The cut off value of ADC for breast carcinoma was 0.792 (sensitivity 98.6%, specificity 65.7%). There was no significant difference in values of ADC for categories of Ki67. There was no significant correlation between ADC mean and Ki67 for all histological subtypes of breast carcinomas (r = 0.156, p = 0.243). Conclusion: ADC cannot be used as a reliable imaging marker for proliferative activity in breast cancer.
Keywords: breast cancer; ADC; DWI; Ki67